Pengaruh Waktu Penyiangan dan Pemangkasan terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis - Siti Khoiriyah; Rusmana Rusmana; Alfu Laila (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Sweet corn (Zea mays sub sp. mays L.) is an essential horticultural commodity that can be consumed fresh or processed. The national production of sweet corn remains variable, so implementing various strategies to enhance crop management during cultivation is crucial. This research aimed to analyze the effect of weeding and pruning timing on the growth and yield of sweet corn. The research was conducted at the Experimental Field of the Faculty of Agriculture, Sultan Ageng Tirtayasa University, Sindang Sari, Pabuaran District, Serang Regency, from February to May 2023. The experiment was designed as a randomized block, consisting of two factors with three replications as blocks. The first factor included weeding times at 0–21, 7–28, and 14–35 days after planting (DAP). The second factor involved pruning time at 45, 50, and 55 DAP. The results indicated no interaction between the duration of weeding and pruning on the growth and yield of sweet corn. Weeding during the 14–35 DAP period significantly increased plant height to 61.31 cm at 28 DAP, actual yield to 3.36 kg·plot-1, and potential yield to 11,238.10 kg·ha-1. Pruning at 50 DAP increased the number of leaves by 10.06 at 56 DAP and delayed male flowering by 50% (53.11 DAP). Therefore, weeding between 14 to 35 DAP and pruning 50 DAP is essential for sweet corn cultivation management practices.